The Impact of the Implementation of an Online Based Hotel Tax Service System Policy on the Effectiveness of Receiving Local Original Revenue (PAD) in Indramayu Regency (Case Study at the Regional Revenue Agency) - Ulya Azkiya; Ismanudin, Ismanudin; Soleh, Soleh (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
Increasing Locally-Generated Revenue (PAD) and Tax Revenue: Hotel taxes can be used for regional development and improving public services. This study analyzes the impact of the implementation of an online-based hotel tax service system policy on the effectiveness of Locally-Generated Revenue (PAD) in Indramayu Regency. Although the online system has been implemented since 2022 on the Indramayu Regency Regional Revenue Agency website, issues such as late payments and reporting by hotel taxpayers persist. The purpose of this study is to examine and analyze the impact of the implementation of an online-based hotel tax service system policy on the effectiveness of locally-generated revenue in Indramayu Regency. The research method used is quantitative. The population of this study was 40 hotels registered in Indramayu Regency. The results of this study indicate that the implementation of the online-based hotel tax service system policy had a moderate effect on the effectiveness of local revenue collection in Indramayu Regency, amounting to 0.474 (47.4%), while the remaining 52.6% was influenced by factors outside this study. Testing the research hypothesis indicates that the implementation of the online-based hotel tax service system policy had a moderate and significant effect on the effectiveness of local revenue collection in Indramayu Regency.